2007
DOI: 10.1002/cbm.644
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the Violence Risk Appraisal Guide (VRAG) in predicting criminal recidivism

Abstract: The validity of the VRAG was replicated with a German sample. The VRAG yielded good predictive accuracy, despite differences in sample and outcome variables compared with its original sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 43 publications
2
20
0
2
Order By: Relevance
“…There is some research on how detected rates vary as a function of some of study features (referred to as calibration; Helmus, ). For example, when there has been a close match between such features in replication studies and the original construction, we reported very close correspondence and successful replication of observed category‐by‐category rates (Harris, Rice, & Cormier, ; Harris et al, ), and some independent studies permit the conclusion of no significant difference between norms and observed rates in new samples (e.g., Kroner, Stadtland, Eidt, & Nedopil, ; Mills, Jones, & Kroner, ; Tengstrom, ). There is no research yet, however, on how the difference between actual recidivism and detected recidivism varies as a function of other factors, such as follow‐up duration.…”
Section: Discussionsupporting
confidence: 54%
“…There is some research on how detected rates vary as a function of some of study features (referred to as calibration; Helmus, ). For example, when there has been a close match between such features in replication studies and the original construction, we reported very close correspondence and successful replication of observed category‐by‐category rates (Harris, Rice, & Cormier, ; Harris et al, ), and some independent studies permit the conclusion of no significant difference between norms and observed rates in new samples (e.g., Kroner, Stadtland, Eidt, & Nedopil, ; Mills, Jones, & Kroner, ; Tengstrom, ). There is no research yet, however, on how the difference between actual recidivism and detected recidivism varies as a function of other factors, such as follow‐up duration.…”
Section: Discussionsupporting
confidence: 54%
“…The advent of actuarial risk instruments such as the Violence Risk Appraisal Guide (VRAG; Quinsey, Harris, Rice, & Cormier, 1998) have contributed mightily to this endeavor. The VRAG is a 12-item actuarial risk assessment tool that has been validated for use in a wide variety of populations such as sex offenders (Harris, Rice, Quinsey, Lalumiere, Boer, & Lang, 2003; Langton, Barbaree, Seto, Peacock, Harkins, & Hansen, 2007), civil psychiatric patients (Harris, Rice & Camilleri, 2004), mentally disordered (Gray, Fitzgerald & Taylor, 2007) and non-North American offender samples (Doyle, Dolan, & McGovern, 2002; Urbaniok, Noll, Grunewald, Steinbach & Endrass, 2006; Kroner, Stadtland & Eidt, 2007). The ability of the VRAG to predict violent behavior among criminal and mentally-disordered male inmates has been well-established (Glover, Nicholson, Bernfeld, & Quinsey, 2002; Kroner & Mills, 2001).…”
mentioning
confidence: 99%
“…Since the majority of the extracted investigations found a significant association with an outcome, the included studies are commonly interpreted as proof of the robustness of the VRAG, SORAG, and Static‐99 (e.g., Hastings, Krishnan, Tangney, & Stuewig, ; Kröner, Stadtland, Eidt, & Nedopil, ) though the purported replication investigations differed with respect to the follow‐up period (Quinsey, Book, & Skilling, ; Rettenberger, Matthes, Boer, & Eher, ), the composition of the study sample (Harris, Rice, & Cormier, ; Hastings et al, ; Snowden, Gray, & Taylor, ), and the definition of the outcome criterion (Endrass, Rossegger, Frischknecht, Noll, & Urbaniok, ; Harris & Rice, ; Harris et al, ; Hastings et al, ; Kroner & Mills, ; Lindsay et al, ; Loza, Villeneuve, & Loza‐Fanous, ; Storey, Watt, Jackson, & Hart, ). Deviations from the methodology used in the development study were interpreted as corroboration of model robustness (Harris & Rice, ; Harris et al, ).…”
Section: Discussionmentioning
confidence: 99%